Knowledge and Perceptions of Muslim Adolescents Regarding Pre-Marital Sexual Relations: A Qualitative Study - Aswadi, Aswadi; Zainuddin , Zainuddin; Syahrir, Sukfitrianty; Adha, Andi Syamsiah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Changes in sexual behavior among teenagers in Indonesia are very worrying. Premarital sexual behavior can have various negative impacts on teenagers. This research aims to determine the knowledge and perceptions of teenagers regarding premarital sexual relations in Gowa Regency. The data collection method used was in-depth interviews. The sample was selected using snowball sampling as many as 7 informants. Data was analyzed qualitatively. The research results showed that the informant's knowledge about reproductive health did not have a positive impact on the informant's sexual behavior, where the informant did not limit risky sexual behavior even though the informant knew the consequences of risky sexual behavior. The informant's perception regarding sexual relations behavior (intercourse) is to seek satisfaction, have fun, the partner must belong completely and also as an expression of affection and love. This study recommends the importance of parental supervision of teenagers' attitudes and behavior through intensive and quality communication without limiting children's rights to mix with their environment. Apart from that, it is necessary to increase the role of parents and religious preachers in providing the best solutions to the problems faced by teenagers using a persuasive approach.